Soldiers of the International a history of the Communist Party of Canada, 1919-1929. - Rodney, William (Canadian studies in history and government, 1968)
Soldiers of the International covers the origins and growth of the Canadian party in detail and shows that its programme and development paralleled those of other Communist parties throughout the world.